Distribution of Phasmarhabditis (Nematode: Rhabditidae) and Their Gastropod Hosts in California Plant Nurseries and Garden Centers - Schurkman, Jacob; Tandingan De Ley, Irma; Anesko, Kyle; Paine, Timothy; Mc Donnell, Rory; Dillman, Adler R. (Frontiers in Plant Science, 2022)
Three species of Phasmarhabditis were recovered from 75 nurseries and garden centers in 28 counties in California during fall and winter 2012-2021. A total of 18 mollusk species were recovered, most of them invasive. Nematodes were identified by sequencing the D2-D3 expansion segments of the large subunit (LSU or 28S) rRNA. Based on these surveys, P. californica was the most widespread species (37 isolates, 53.6% recovery); followed by P. hermaphrodita (26 isolates; 37.7% recovery); P. papillosa and a closely related P. papillosa isolate (6 isolates; 8.7% recovery). Nematode isolates were mainly collected from four invasive slugs (Deroceras reticulatum, D. laeve, Arion hortensis agg, Ambigolimax valentianus) and snails (Oxychilus sp and Discus sp). Results suggest that P. californica and P. hermaphrodita share an ecological niche in Northern, Central, Coastal CA, and Southern CA, north of Los Angeles County.